"We no longer fear brides from afar": Marriage markets and gendered mobilities in rural Vietnam. (September 2019) - Bélanger, Danièle; Haemmerli, Guillaume
Since the late 1990s, Vietnamese women's participation in international marriage migration has garnered academic and media attention. In contrast, internal marriage migration, a key driver of overall internal migration flows, has received scant consideration. In this paper, we examine marriage and migration dynamics in four rural communes that have "lost" significant numbers of their single women to international marriage and gained brides through internal migration. Based on ethnographic fieldwork conducted in 2012 and 2013 in four villages and analysis of local marriage registration data and census data, this article examines internal and international marriage migration. We probed marriage migration vis-a-vis marriage markets, internal labor migration and gendered mobility patterns. The increased diversification of marriage with respect to spousal places of origin indicates a reconfiguration of marital norms and practices and changing social constructions of a desirable wife and daughter-in-law. Results underscore the role of labor migration and interprovincial networks in expanding mate-seeking circles among rural youth and in altering marital norms. Female international marriage migration is one piece of a larger puzzle whereby various forms of mobility are intertwined with changes in the realms of gender, family and marriage.